Transcriptome-Wide Characterization of Seed Aging in Rice: Identification of Specific Long-Lived mRNAs for Seed Longevity - Wang, Bingqian; Wang, Songyang; Tang, Yuqin; Jiang, Lingli; He, Wei; Lin, Qinlu; Yu, Feng; Wang, Long (Frontiers in Plant Science, 2022)
Various long-lived mRNAs are stored in seeds, some of which are required for the initial phase of germination and are critical to seed longevity. However, the seed-specific long-lived mRNAs involved in seed longevity remain poorly understood in rice. To identify these mRNAs in seeds, we first performed aging experiment with 14 rice varieties, and categorized them as higher longevity (HL) and lower longevity (LL) rice varieties in conventional rice and hybrid rice, respectively. Second, RNA-seq analysis showed that most genes showed similar tendency of expression changes during natural and artificial aging, suggesting that the effects of these two ageing methods on transcription are comparable. In addition, some differentially expressed genes (DEGs) in the HL and LL varieties differed after natural aging. Furthermore, several specific long-lived mRNAs were identified through a comparative analysis of HL and LL varieties after natural aging, and similar sequence features were also identified in the promoter of some specific long-lived mRNAs. Overall, we identified several specific long-lived mRNAs in rice, including gibberellin receptor gene GID1, which may be associated with seed longevity.